Tell A Church - Lessons Learned From a Church- based Tuberculosis Health Education Program - Atiba Nelson; Robin Lewy; Francine Ricardo (University of North Florida, 2008)
Historically, the church has been the center of the African American community - contributing to the spiritual and physical well-being of its congregations. Community health education outreach utilizing African American churches could prove effective but is often neutralized by historical feelings of distrust in research and outreach by secular organizations. During the summer of 2007, the "Think TB" project, a tuberculosis education program, attempted to utilize the church as a health education venue and overcome the historical hurdles that usually hamper church- based health education promotion. This paper discusses the "Think TB" program's challenges and successes.